UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN SOSIOLOGI SUB MENGANALISIS DAMPAK PERUBAHAN SOSIAL TERHADAP KEHIDUPAN MASYARAKAT MELALUI METODE EKSPOSITORI PADA SISWA KELAS XII.IPS4 SMA N 1 KINALI - dasimar dasimar (STKIP Pesisir Selatan, 2017)
ABSTRACTBased on the results of student learning XII.IPS4 Class SMA N 1 Kinali in the subjects of Sociology sub Analyzing the impact of social change on people's lives is found that results for students in the subjects of Sociology sub Analyzing the impact of social change on people's lives is still very low. The average student learning outcomes are still under KKM. The purpose of this study is to describe and obtain information about efforts to improve student learning outcomes in subjects Sociology sub Analyzing the impact of social change on people's lives through Expository Method in class XII.IPS4 SMA N 1 Kinali Pasaman Barat.This research is a class act. The procedure in this research include planning, action, observation and reflection. The study consisted of two cycles of the four meetings. Subjects consisted of 32 learners XII.IPS4 Class SMA N 1 Kinali. Data were collected by using observation sheet and daily tests. Data were analyzed using percentages.Based on the results of research and discussion that has been raised, it can be concluded that the Expository method can improve student learning outcomes in subjects Sociology sub Analyzing the impact of social change on people's lives in SMA N 1 Kinali. Learning outcomes of students from the first cycle to the second cycle. The results of students in the first cycle was 60.06 (Enough) increased to 80.81 (Good) with an increase of 20.75%.Keywords: Learning Outcomes, Sociology, Methods Expository